Bridging the digital disability divide: supporting digital participation of individuals with speech, language, and communication disorders as a task for speech-language pathology - Thorndahl, Dennis; Abel, Miriam; Albrecht, Katharina; Rosenkranz, Anna; Jonas, Kristina (Frontiers in Communication, 2025)
PurposeThe goal of speech-language pathology is to ensure and improve the participation of individuals with speech, language, and communication disorders. Continued digital transformation means more participation occurs through digital media, raising questions about the digital participation of these individuals and the role, content, and framework of speech-language pathology, both of which need proactive discussion. This Perspective Article outlines a viewpoint on these developments, aiming to stimulate critical reflection and disciplinary dialog on the future role of speech-language pathology in the digital age.ConclusionResearch indicates that individuals with speech, language, and communication disorders are restricted in their digital participation. There is a lack of comprehensive understanding regarding the impact of various speech, language and communication skills on digital participation across different disorders. If speech-language pathology aims to promote participation and this is increasingly dependent on digital media and information and communication technologies (ICTs) then digital participation must also be a therapeutic goal. Achieving this requires more (participatory) research and corresponding training opportunities for speech language pathologists (SLPs).